Effects of different soil tillage systems and coverages on soybean crop in the Botucatu Region in Brazil - Rodrigues, J. G. Lanca [UNESP]; Gamero, Carlos Antonio [UNESP]; Fernandes, J. Costa [UNESP]; Miras-Avalos, J. M. (Spanish Natl Inst Agricultural & Food Research & Technolo, 2009)
Nowadays, agricultural practices should combine high yields with a sustainable use of resources. Different tillage practices and crop covers, if combined, may help to achieve both objectives. In this work, several traits of a soybean (Glycine max L. Merr) cultivar were studied under different conditions of tillage and previous soil coverages. The experiment was installed at Lageado Research Station, Botucatu county, SP, Brazil, on a Paleudult. It consisted of nine treatments (combining three systems of soil tillage and three cover crops) and 4 replicates, yielding 36 plots of a randomized block experimental design. The soil tillage systems considered were: (i) conventional tillage with two heavy harrowing and a levelling harrowing; (ii) chiseling, and (iii) no-tillage with chemical drying of vegetation. The three cover crops used were: black oat, sorghum and spontaneous vegetation. Analyzed variables were: plant height, initial and final plant densities, height of first pod insertion, weight of a thousand grains, number of pods per plant, number of grains per pod, and crop yield. No significant differences were observed for most of the analyzed variables; however, conventional tillage produced significantly heavier grains and a higher number of pods per plant. The selected covers were considered an excellent coverage prior to planting soybean in a crop rotation. The three tillage systems can be used for deployment of culture without compromising the development of soybean.
Keywords: black oat; chisel; Glycine max; heavy harrow; sorghum; yield